2015
DOI: 10.1590/s0100-736x2015000100016
|View full text |Cite
|
Sign up to set email alerts
|

Influência da qualidade microbiológica da água de dessedentação na morfologia intestinal de frangos de corte

Abstract: Para avaliar se a qualidade microbiológica da água de dessedentação intervém na morfologia intestinal de frangos de corte, foram analisados o consumo semanal de água, a microbiologia de amostras de água, a microscopia eletrônica de varredura e a histologia do intestino delgado de frangos de corte tratados com água filtrada e não filtrada. Os frangos que ingeriram água filtrada tiveram acesso ao menor número de micro-organismos fecais (2,52±0,99 Número Mais Provável (NMP) de coliformes fecais e 1,17±1,25 NMP de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Regarding water quality, it is common practice to provide chlorinated water and to clean pendular drinkers at least twice every day. Amoroso et al (2015) reported a higher number of coliforms and E. coli in unfiltered water with possible fecal contamination. E. coli can result in poor performance of chickens, which can be prevented by supplementation with probiotic and synbiotics, as these additives weaken the inflammatory response to bacteria (Ateya et al 2019).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding water quality, it is common practice to provide chlorinated water and to clean pendular drinkers at least twice every day. Amoroso et al (2015) reported a higher number of coliforms and E. coli in unfiltered water with possible fecal contamination. E. coli can result in poor performance of chickens, which can be prevented by supplementation with probiotic and synbiotics, as these additives weaken the inflammatory response to bacteria (Ateya et al 2019).…”
Section: Resultsmentioning
confidence: 96%
“…In addition, birds subjected to the sanitary challenge likely ingested a greater amount of coliforms, because of the poor quality of the water provided (without chlorine and containing organic matter and/or excreta because of unclean drinkers). According to Amoroso et al (2015), untreated and poor-quality water contains a higher number of coliforms, including E. coli. However, the additives did not alter the Enterobacteriaceae population, which was consistent with the observations of Sherief et al (2012), who did not report any effect of probiotics and synbiotics on the total count of coliforms, Escherichia coli, or aerobic bacteria.…”
Section: Resultsmentioning
confidence: 99%